2015
DOI: 10.1097/acm.0000000000000778
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting Primary Care Physicians to Teach Medical Students in the Ambulatory Setting

Abstract: A qualitative study to describe the barriers to and solutions for recruiting physicians to teach students in ambulatory settings is planned. Other studies will evaluate the effectiveness of faculty development efforts and the impact of students' presence on patients' access to clinic appointments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 4 publications
2
18
0
Order By: Relevance
“…1,2 Despite the need for robust ambulatory education, internal medicine educators face well-documented difficulties in recruiting ambulatory training sites for both students and residents. 3,4 Barriers include increasing physician workload, inadequate financial support, and competition from other learners. In response to this growing concern, a task force was convened by the Alliance of Academic Internal Medicine and Society of General Internal Medicine in 2016.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Despite the need for robust ambulatory education, internal medicine educators face well-documented difficulties in recruiting ambulatory training sites for both students and residents. 3,4 Barriers include increasing physician workload, inadequate financial support, and competition from other learners. In response to this growing concern, a task force was convened by the Alliance of Academic Internal Medicine and Society of General Internal Medicine in 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, employers of all pharmacists must emphasize the importance of lifelong learning and develop an organizational culture that exemplifies this by engaging individuals at all levels of the organization 110,114,115 …”
Section: Part 3: Program Development and Implementationmentioning
confidence: 99%
“…Finally, our project benefited significantly from institutional support to pursue coaching; both faculty members serving as coaches had built-in flexibility to their academic schedules to pursue projects to improve the quality of ambulatory resident education. Previous work has shown that the quality of clinical teaching is linked to the amount of protected time in academic settings [19,20].…”
Section: Critical Reflectionmentioning
confidence: 99%